2023
DOI: 10.3389/fped.2023.1060311
|View full text |Cite
|
Sign up to set email alerts
|

The deadly impact of COVID-19 among children from Latin America: The case of Ecuador

Abstract: BackgroundThe SARS-CoV-2 pandemic remains a critical global health concern, with older adults being the most vulnerable group. Nonetheless, it is crucial to recognize that COVID-19 has caused numerous deaths in children worldwide. Emerging evidence indicates that infants and breastfeeding children, particularly those aged below one year, face a greater risk of hospitalization and mortality than older children with COVID-19.ObjectiveThis study aimed to describe the epidemiology of COVID-19 among children during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the same period, this study found that most deaths occurred in children aged 0 to 1 year, representing 44% (n = 114) of total deaths reported. of the total number of hospitalized under 19-year-olds [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the same period, this study found that most deaths occurred in children aged 0 to 1 year, representing 44% (n = 114) of total deaths reported. of the total number of hospitalized under 19-year-olds [17].…”
Section: Discussionmentioning
confidence: 99%